Religion and HIV and AIDS : charting the terrain - Haddad, Bev. (Scottsville : University of Kwazulu-Natal Press, 2011)
Introduction. Cartography of HIV and AIDS, religion and theology: an overview / Beverley Haddad. Pt. 1. Engaging the public realm. 1. Religion and medicine in the context of HIV and AIDS: a landscaping review / Jill Olivier and Gillian Paterson. Practitioner response / Greg Manning -- 2. HIV, AIDS and religion in sub-Saharan Africa: an historical survey / Philippe Denis. Practitioner response / Alison Munro -- 3. Religion and policy on HIV and AIDS: a rapidly shifting landscape / Jill Olivier. Practitioner response / Bongi Zengele -- 4. Statements by religious organisations on HIV and AIDS: intersecting the public realm / Martha Frederiks. Practitioner response / Paula Clifford. Pt. 2. Engaging the religious and theological realm. 5. Sacred texts, particularly the Bible and Qur'an and HIV and AIDS: charting the textual territory / Gerald West. Practitioner response / Monica Jyotsna Melanchthon -- 6. Systematic theological reflection on HIV and AIDS: mapping the terrain / Steve de Gruchy. Practitioner response / Jan Bjarne Sd̜al -- 7. Comparative ethics and HIV and AIDS: interrogating the gaps / Domoka Lucinda Manda. Practitioner response / Farik Esack -- 8. Missiology and HIV and AIDS: defining the contours / Ute Hedrich. Practitioner response / Benson Okyere-Manu. Pt. 3. Engaging the socio-cultural realm. 9. African traditional religions and HIV and AIDS: exploring the boundaries / Ezra Chitando. Practitioner response / Phumzile Zondi-Mabizela -- 10. African cultures and gender in the context of HIV and AIDS: probing these practices / Nyokabi Kamau. Practitioner response / Ezra Chitando -- 11. Transforming masculinities towards gender justice in an era of HIV and AIDS: plotting the pathways / Adriaan van Klinken. Practitioner response / Lilian Silwa -- 12. Children seldom seen and heard: identifying the religious HIV and AIDS discourse / Genevieve James. Practitioner response / Bongi Zengele. Pt. 4. Engaging the communal realm. 13. Religion and HIV prevention: surveying the contestations / Greg Manning. Practitioner response / Johannes Petrus Mokgethi-Heath -- 14. HIV, AIDS and stigma: discerning the silences / Gillian Paterson. Practitioner response / Gideon Byamugisha -- 15. Religious community care and support in the context of HIV and AIDS: outlining the contours / Jill Olivier and Paula Clifford. Practitioner response / Edwina Ward -- 16. Stories of hope: navigating HIV pathways of life / Phumzile Zondi-Mabizela ... [et al.]
Includes bibliographical references and index.
Keywords: AIDS (Disease) -- Religious aspects; AIDS (Disease) -- Religious aspects -- Christianity; AIDS (Disease) -- Religious aspects -- Islam; HIV infections -- Religious aspects; HIV infections -- Religious aspects -- Christianity; HIV infections -- Religious aspects -- Islam